1984
DOI: 10.1111/j.1470-6431.1984.tb00425.x
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetic Rules in Women's Apparel: Empirical Fact or Fantasy

Abstract: Aesthetic rules derived from ancient Greece abound in college textbooks used in modern apparel design and selection courses. This study attempted to evaluate these aesthetic rules empirically. Based on measurements of six persistent features (skirt length, waist length, décolletage length, skirt width, waist width, décolletage width) of women's evening apparel from 1926 to 1980, the distribution of frequencies for each dress dimension was not uniform but demonstrated a preferred value or region. Likewise, not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 0 publications
2
18
0
Order By: Relevance
“…Limited numbers of studies have focused on proportion in apparel. Lowe (1984) studied proportions of evening wear and tested proportion rules, including the golden section found in apparel design textbooks. She also examined balance or the "equalization of attractions on either side of a centered vertical line or from top to bottom" (p. 169).…”
Section: Proportion Rulesmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited numbers of studies have focused on proportion in apparel. Lowe (1984) studied proportions of evening wear and tested proportion rules, including the golden section found in apparel design textbooks. She also examined balance or the "equalization of attractions on either side of a centered vertical line or from top to bottom" (p. 169).…”
Section: Proportion Rulesmentioning
confidence: 99%
“…Other rules related to apparel, such as symmetry, in which the left and right sides appear to be visually equal on either side of a vertical line or asymmetry in which the left and right sides appear to be visually unequal, are usually discussed in textbooks. There are few studies of these rules related to apparel (Lowe, 1984).…”
mentioning
confidence: 99%
“…This approach has been used in previous visual analysis research (DeLong & Cerny, 1983-1984DeLong & Minshall, 1988;DeLong, Salusso-Deonier, & Lartnz, 1983). This approach has been used in previous visual analysis research (DeLong & Cerny, 1983-1984DeLong & Minshall, 1988;DeLong, Salusso-Deonier, & Lartnz, 1983).…”
Section: Interval Measurementmentioning
confidence: 99%
“…Although the majority of visual analysis studies reviewed did not evaluate instrument reliability, the studies that employed semantic differential scales (DeLong & Cerny, 1983-1984DeLong & Larntz, 1980;DeLong & Minshall, 1988;DeLong, Salusso-Deonier, & Lartnz, 1983) did attempt to evaluate the consistency with which larger groups of subjects utilized these measures in their assessments of pictures of clothing. In general, these studies concluded that semantic differential scales were useful in measuring collective perceptions of clothing.…”
Section: Instrument Limitations and Recommendations For Future Use LImentioning
confidence: 99%
“…While sizing is based upon proportional ideals, fashion designers of the present century disregard aesthetic rules derived from the Greek ideal of proportional relationships when designing stylistic variations of apparel (Lowe, 1984;Lowe 1991). Lowe (1984) queried why the proportional order demonstrated in her study was so different from that predicted by existing proportional rules based upon the Greek ideal, the golden mean.…”
mentioning
confidence: 99%